Analysis of the Effect of Open Unemployment Rate, Poverty Rate, and Economic Growth on the Human Development Index (HDI) - Zulfalinda, Azzahra; Damayanti, Ayu (Journal of Business Management and Economic Development, 2025)
This study aims to analyze the influence of open unemployment, poverty levels, and economic growth on the Human Development Index (HDI). HDI serves as a crucial indicator reflecting the quality of life in terms of health, education, and a decent standard of living. Utilizing time series data from 2013 to 2022 and employing multiple linear regression analysis, this research examines the relationship between these macroeconomic variables and human development achievements. The findings reveal that both poverty and open unemployment have a significant negative impact on HDI, while economic growth does not show a statistically significant effect. These results suggest that improving human development quality is not solely dependent on economic growth, but is strongly influenced by lower levels of unemployment and poverty. Therefore, policy strategies focused on reducing unemployment and poverty are essential to sustainably enhance human development.